THE END OF THE PARTIES COALITIONS DUE TO THE CONSTITUTIONAL AMENDMENT Nº 97/2017: ANALYSIS ABOUT ITS CONSEQUENCES IN THE PROPORTIONAL ELECTIONS - Angelo Aranega Garcia, Miguel; Carmo, Valter Moura do (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2021)
The present article aims to analyse the consequences of the prohibition of party coalitions in the proportional elections after the constitutional amendment nº 97/2017 promulgation. In this context, it discusses the parties’ creation and operation since 1979´s Electoral Reform, yet during the last military government, and how the national parties’ life followed it, with the re-democratization of the country and the consolidation of the Brazilian democratic system. To build the topic’s discussion, exploratory research based on a bibliographic survey was used. Thus, the functioning of the proportional electoral system in Brazil was detailed, as well as how the election to fill the positions in the Legislative works. The article is guided by a critical analysis of the party coalition institute, as well as by the reasons for its prohibition and the electoral consequences of this prohibition in the elections to be held in 2020. Lastly, the influence of this prohibition in the rearrangement of the national political parties was also considered.